Working and housing conditions of human resources in a dairy farm in Santa Fe, Argentina. - SUERO, M. (Universidad Nacional del Litoral, 2019)
The present article analyzes the working and housing conditions of the dairy operators of the companies that integrate the “Central United Limited Dairy Cooperative” from San Guillermo, province of Santa Fe. The importance of this analysis lies in the fact that human resources are fundamental to ensure competitiveness of the milk production systems. To carry out this proposal, interviews were administered to producers and businessmen, and to dairy farmers and operators using the case study as the research methodology. The results obtained allowed us to conclude that the housing and working conditions, as well as the environmental aspects have a major influence upon the performance of operators. Besides, the impact of these factors depends on the company production scale